A CLINICAL TRIAL OF AROGYA VARDHINI VATI AND LEKHANIYA MAHAKASHAYA IN THE MANAGEMENT OF OBESITY (AYUSHDHARA, 2018)
Obesity is a condition in which there is an excessive accumulation of fat in the body which is a risk to health. The WHO now considers obesity to be a global epidemic and public health problem. Globally an estimated 300 million adults are now obese and many are overweight. A person with a BMI of 30 or more is generally considered obese. The problem is due to calorie imbalance resulting from an excessive food intake coupled with inadequate exercise. It is associated with increased mortality by predisposing to the development of important diseases like diabetes, hypertension, atherosclerosis, heart diseases, arthritis, infertility etc and diminishes the efficacy and happiness of affected. As per Ayurveda, Acharya charaka has counted Sthoulya under the eight varieties of impediments which are designated as Ninditapurusha. As Chikitsa sutra of Sthoulya, Lekhan karma is an important therapeutic measure said by Acharya charaka. Moreover, drugs of Arogya vardhini vati and Lekhaniya mahakashaya are most effective in the management of Sthoulya. To assess the effect of Lekhan karma, 20 patients were selected for this study from the OPD and IPD of Uttarakhand Ayurved University, Gurukul Campus Hospital, Haridwar. The effect of the therapy was assessed statically based on the performa prepared.